Answer:
(x+4)(x-2)
Step-by-step explanation:
We need to find two numbers that multiply to -8 and add up to 2. These are 4,-2.
Rewrite the polynomial:
x^2-2x+4x-8
and factor each pair:
x(x-2)+4(x-2) = (x+4)(x-2)
4(×+2)=
3 (a+2)=
2 (×+3)=
Answer:
4(x+2) = 4*x + 4*2 = 4x+8
3(a+2) = 3*a + 3*2 = 3a + 6
2(x+3) = 2*x + 2*3 = 2x +6
Hope this help you :3
Step-by-step explanation:
Use the distributive property a(b + c) = ab + ac
4(x + 2) = (4)(x) + (4)(2) = 4x + 8
3(a + 2) = (3)(a) + (3)(2) = 3a + 6
2(x + 3) = (2)(x) + (2)(3) = 2x + 6
Answer:
Step-by-step explanation:
All sides of a triangle equel 180 degrees, so 180-60-55=115. 180-115 is 65. 65-20-45. Hope this works!
Answer:
The answer in the procedure
Step-by-step explanation:
Let
x------> the number of minutes
y------> the depth in feet
In this problem the relationship between the variables, x, and y, represent a proportional variation
Remember that
A proportional variation if it can be expressed in the form or
In a proportional relationship the constant of proportionality k is equal to the slope m of the line and the line passes through the origin
so
step 1
Find the value of k
Let
------> see the given table
----> substitute the values
The direct variation equation is equal to
step 2
Complete the table
For
substitute the value of x in the equation and solve for y
step 3
Complete the table
For
substitute the value of y in the equation and solve for x
Answer:
The cost in dollars and the amount of yogurt are proportional
Step-by-step explanation:
Proportions
Two variables are proportional if the ratio or division between them is a constant value.
Kareem buys a 32-oz container of yogurt for $2.56. We can compute the ratio of the quantity of yogurt and price 32/2.56 and we get 12.5. Jonah buys a 6-oz container of yogurt for $0.48. The relation is now 6/0.48=12.5
Since both ratios are equal, we can say the amount of yogurt, and the cost in dollars are proportional variables
Answer:
Step-by-step explanation:
Given;
Slope m= 4
y-intercept c= 4
equation of line= y= mx+c
y=4*x+4
y=4x+4
-4x+y-4=0